Enhancing EFL Students' Speech Presentation Skills through Aristotle's Rhetoric - Takegami, Fumi (Advances in Social Sciences Research Journal, 2024)
This study explores the enhancement of EFL (English as a Foreign Language) students' speech presentation skills through principles of Aristotle's classic work, titled Rhetoric. By fostering metacognitive awareness of rhetoric, students gain insight into the purpose and benefits of speech activities, leading to improved public speaking and language fluency. Additionally, metacognition equips students with the skills to structure their efforts towards successful completion of speech activities, ensuring more effective and confident presentations. Introducing Aristotle’s three modes of persuasion—ethos, pathos, and logos—provides a framework for structuring speeches and evaluating others’ presentations. This metacognitive approach also benefits teachers, offering a deeper understanding of rhetorical principles rooted in the classic work on making persuasive speech presentations. The study proposes scaffolded lesson plans to integrate these rhetorical strategies into EFL instruction, demonstrating that such integration enhances students' ability to develop and deliver effective speeches. Ultimately, this pedagogical approach promotes learner autonomy and proficiency in public speaking by applying theoretical constructs to practical classroom activities.